Analisis Pengaruh Kemiskinan Dan Pengangguran Terhadap Pertumbuhan Ekonomi Di Tapanuli Selatan - Nasution, Fitri Sari Ramdhani; Sahnan, M.; Naeruz, Mila (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2024)
The    problem   formulation   of   this   research   is   whether   poverty   has   an   effect   on economic   growth,   and   whether   unemployment   has   an   effect   on   economic   growth in   South   Tapanuli   Regency .   The   aim   of   this   research   is   to   find   out   how   the level   of   poverty   and   unemployment   influences   economic   growth.   This   research was   conducted   in   South   Tapanuli   Regency.   The   technical   analysis   of   this research   is   quantitative   analysis   using   classical   and   multiple   linear   assumption tests.    The   data   source   used   in   this   research   is   secondary   data   downloaded   via the   official   website   of   the    Central   Statistics   Agency   ( BPS ),   especially   data   on the   number   of   poverty   in   South   Tapanuli   Regency   and   data   on   the   number   of unemployed.   and   data   on   economic   growth.   Based   on   the   results   of   research that   has   been   conducted,   it   shows   that   poverty   and   unemployment   have   a positive   or   significant   effect   on   economic   growth   in   South   Tapanuli   Regency.   It can   be   seen   that   the   Fcount   value   is   14.955   and   the   Sig   value.   is   0.002.   In the   F   distribution   table,   the   Ftable   value   obtained   at   α   =    0.05   with   df1   ( df regression )   =   2   and   df2    (  residual df  )   =   3 is 9.5.   This   shows   that   the   Fcount value   ( 14.955 )   Ftable   ( 9.55 )   and   the   Sig   value   0.002      0.05.   So   it   can   be   concluded   that   H0   is   rejected   and   Ha   is   accepted,   meaning   that   the   poverty level   and   unemployment   rate   simultaneously   have   a   significant  effect   on   economic   growth   in   South   Tapanuli.The    problem   formulation   of   this   research   is   whether   poverty   has   an   effect   on economic   growth,   and   whether   unemployment   has   an   effect   on   economic   growth in   South   Tapanuli   Regency .   The   aim   of   this   research   is   to   find   out   how   the level   of   poverty   and   unemployment   influences   economic   growth.   This   research was   conducted   in   South   Tapanuli   Regency.   The   technical   analysis   of   this research   is   quantitative   analysis   using   classical   and   multiple   linear   assumption tests.    The   data   source   used   in   this   research   is   secondary   data   downloaded   via the   official   website   of   the    Central   Statistics   Agency   ( BPS ),   especially   data   on the   number   of   poverty   in   South   Tapanuli   Regency   and   data   on   the   number   of unemployed.   and   data   on   economic   growth.   Based   on   the   results   of   research that   has   been   conducted,   it   shows   that   poverty   and   unemployment   have   a positive   or   significant   effect   on   economic   growth   in   South   Tapanuli   Regency.   It can   be   seen   that   the   Fcount   value   is   14.955   and   the   Sig   value.   is   0.002.   In the   F   distribution   table,   the   Ftable   value   obtained   at   α   =    0.05   with   df1   ( df regression )   =   2   and   df2    (  residual df  )   =   3 is 9.5.   This   shows   that   the   Fcount value   ( 14.955 )   Ftable   ( 9.55 )   and   the   Sig   value   0.002      0.05.   So   it   can   be   concluded   that   H0   is   rejected   and   Ha   is   accepted,   meaning   that   the   poverty level   and   unemployment   rate   simultaneously   have   a   significant  effect   on   economic   growth   in   South   Tapanuli